Kontribusi pengetahuan ibu dan praktik asi eksklusif terhadap status gizi balita di Desa Pinggirsari Kecamatan Ponorogo - Selli Ayu Riyani; Stefunny Icha Mahaputri (Journal of Health and Therapy, 2024)
Stunting and toddler nutrition issues remain a concern because they can affect children's growth and development. This study aims to determine the relationship between maternal knowledge and exclusive breastfeeding with toddlers' nutritional status in Pinggirsari Village, Ponorogo District. This study used an analytical, cross-sectional design. The study sample comprised mothers with toddlers in Pinggirsari Village, Ponorogo District, and was selected using a simple random sampling technique. Data analysis used the Spearman test. The results showed that most mothers had a good level of knowledge, the majority of toddlers received exclusive breastfeeding, and most toddlers had good nutritional status. This study showed no relationship between maternal knowledge and toddler nutritional status, whereas a history of exclusive breastfeeding was associated with toddler nutritional status. It is recommended that mothers of toddlers apply nutritional knowledge in their daily lives, provide exclusive breastfeeding for 6 months, and continue complementary foods according to the child's age.